Algeria - Public Expenditure Review : Assuring High Quality Public Investment, Volume 2. Annexes and Statistical Annex - World Bank (Washington, DC, 2012)
The fiscal space generated by a prolonged oil windfall has enabled Algeria to embark on a massive public investment program for 2005- 09, Programme Complementaire de Soutien a la Croissance (PCSC). Taking advantage of the current macroeconomic and fiscal opportunity, the country could institutionalize high-quality public expenditure that would contribute social benefit far into the future. This Public Expenditure Review (PER) is an exercise to help the Government toward that end. The objectives of this PER are to assist the government in the following: evaluate fiscal sustainability in light of the country's fiscal push that PCSC represents; set high technical standards for public investment management; draw lessons from the on-going budget modernization reform in order to support the overall implementation, monitoring, and evaluation of projects; support the preparation of a medium-term expenditure framework and improve the efficiency and cost-benefit of investments in four key sectors, transport and public works, water, education, and health.